PREVALENCE OF METHICILLIN-RESISTANT STAPHYLOCOCCUSAUREUS (MRSA) IN COMMUNITY-ACQUIRED PRIMARY PYODERMA - Ali, Mariam K (Al-Nahrain Journal of Science, 2010)
Although prevalence of MRSA strains is reported to be increasing, there are no studies of their prevalence in community-acquired primary pyodermas in Iraq.Aims: This study aimed at determining the prevalence of MRSA infection in community-acquired primary pyodermas.Methods: prospective survey carried out in Dermatology Department of Baghdad Teaching Hospital in Baghdad.Materials and Methods: Eighty-six patients with primary pyoderma, visiting the dermatology outpatient, were studied clinically and microbiologically. Sensitivity testing was done for vancomycin, sisomycin, gentamicin, framycetin, erythromycin, methicillin, cefazolin, cefuroxime, penicillin G and ciprofloxacin.Results: The culture positivity rate was 83.7%. Staphylococcus aureus was isolated in all cases except two. Barring one, all strains of Staphylococcus aureus were sensitive to methicillin. Conclusions: Methicillin resistance is uncommon in community-acquired primary pyodermas in Baghdad. Treatment with antibacterial active against MRSA is probably unwarranted for community-acquired primary pyodermas.